Postural Drainage Intervention in Reducing Dyspnea among Bronchial Asthma Patients at Maccini Sawah Public Health Center - Nurhayati, Nurhayati; D, Andina; Nurbaiti, Nurbaiti; Kasim, Erna (Inspirasi Foundation, 2025)
Introduction: Bronchial asthma is a chronic respiratory condition marked by airway inflammation, mucus hypersecretion, and bronchial spasms, resulting in dyspnea and decreased respiratory efficiency. Postural drainage, a form of chest physiotherapy, has been suggested as a nonpharmacological intervention to enhance mucus clearance and reduce respiratory distress. Objective: This study aimed to assess the effectiveness of postural drainage therapy in reducing dyspnea among patients with bronchial asthma at the Maccini Sawah Public Health Center. Method: A descriptive case study design was employed, involving two asthma patients observed over three consecutive days. Postural drainage was implemented using three different positions across three sessions per participant. Data were collected through observation using the Medical Research Council (MRC) Dyspnea Scale, interviews, and documentation. The effect of the intervention was evaluated by comparing pre- and post-intervention dyspnea levels. Result: Both participants demonstrated a consistent reduction in dyspnea levels following the intervention. On the first day, each respondent exhibited moderate shortness of breath (MRC score: 2), which progressively improved by the third day to a score of 0, indicating no dyspnea. Improvements were also reflected in vital signs, including reduced respiratory rate and more stable pulse. The intervention was well tolerated, and participants reported subjective relief in breathing. Conclusion: Postural drainage is a safe, effective, and easily administered intervention that significantly reduces dyspnea in bronchial asthma patients. It holds promise as a supportive therapy for asthma management and should be considered in clinical practice, especially in community healthcare settings.